CAROTID ARTERY STENTING IN A PATIENT WITH SINUS BRADYCARDIA: CLINICAL CASE - E. S. Bulgakova; T. V. Tvorogova; B. A. Rudenko; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Syndrome of hemodynamic depression is a frequent complication of the carotid artery endovascular intervention and, as a rule, is transient in nature. This article presents a clinical case of carotid artery stenting in a 63-year-old patient. The specific feature of this patient was the initial sinoatrial node dysfunction as a permanent sinus bradycardia. The examination verified multisite atherosclerosis, including coronary artery stenosis, manifested by the presence of stable angina, without history of myocardial infarction. Therefore, coronary endovascular treatment was firstly performed. Reexamination after coronary blood flow restoration revealed stable sinus bradycardia persistence without any positive or negative changes. According to anamnesis, examination and instrumental diagnostic results, indications for permanent cardiac pacing were not identified. Carotid artery stenting after the necessary preventive measures was successful. The article also considers possible risk factors of significant perioperative bradycardia during carotid angioplasty with stenting and measures preventing cardiac conduction perioperative worsening.